A Study of Parents’ Expectation and Satisfaction towards School Management in Nopparatpattanasas School, Bangkok Thailand - Pungbangkradee, Nopparat; Eamoraphan, Suwattana (Scholar: Human Sciences, 2016)
The purpose of this study was to study of parents’ expectation and satisfaction towards school management in Nopparatpattanasas School, Bangkok, Thailand. The results showed that the level of parents’ expectation and satisfaction towards school management were “Agree”. The finding of the hypotheses research found that, there was a significant difference between parents’ expectation and satisfaction of school management, and four dimensions, and there was a significant difference between kindergarten level parents’ expectation and satisfaction in school management, and there was a significant between elementary level parents’ expectation and satisfaction of school management. The results of this study showed that most of the parents were satisfied with the school management in term of human resource management and general management. Based on the finding, the researcher recommended that Nopparatpattanasas School should emphasize on the curriculum management and the budget management.